Caracterização físico-ambiental da Microbacia Hidrográfica do Riacho Trapiá/Jacutinga, Recôncavo Sul – BA - Oliveira, Nilton de (2003)
This work objectives the study of the physical environment of the hydrographic microbasin of the Trapiá- Jacutinga river (BHRTJ), that integrates the hydrographic basin of the Jequiriçá river. This system is located in the South Hollow of the State of Bahia and is composed of a network of small everlasting affluents, intermittent and ephemeral , that drain the lands of the Bahia municipalities of Amargosa, Elísio Medrado and Santa Terezinha, totalling an area of 143,9 km2. The studies focated geology, geomorphology, original vegetation and use nowadays, the geography of soils , morphometric studies and, at last a socialenvironmental diagnosis was made in a space considered of utmost importance in that system, since it is an area of input of the main everlasting affluents of the BHRTJ, with high rate of population as related to the other areas. The results achieved and discussed allow to state the following conclusions: The Tand tertiary sediments in the other areas; the geomorphology is dominated by plateaus in different stages of dissection and by mountain chains; the main soils of the BHRTJ are typical Yellow Cohesive Latosoils, dystrophic Red-Yellow Latosoils, typical Haplic Sodic Cambisoils, eutrophic Red-Yellow Claysoils and Lytholic Neosoils. The BHRTJ presents a standard of dentritic drainage and channels of 1o, 2o, 3o and 4o orders. The socialenvironmental diagnosis made in the area above the dam in the location of Jacutinga has shown an advanced stage of degradation of soil and water resources and also that almost all proprietors ignore fundamental cares related to the use of natural resources sustainedly.